Respuesta :
Question 1
M + 4 = -M + 10
First reorganize the terms on the left side
M + 4 = 10 - M
Take away 4 from both sides
M + 4 - 4 = 10 - M - 4
M = 10 - M - 4
Combine positive 10 and negative 4
M = 6 - M
Add M to both of the sides
M + M = 6 - M + M
M + M = 6
2M = 6
Divide both sides by 2
2M/2 = 6/2
M = 3
Question 2
2x - 2 = x - 4
Take away 1x from both sides of the equation
2x - 2 = x - 4
2x - 1x - 2 = x - 1x - 4
1x - 2 = -4
x - 2 = -4
Add 2 to both of the sides of the equation
x - 2 + 2 = -4 + 2
x = -2
Question 3
5n - 9 = 4n + 2
Add 9 to both sides of the equation
5n - 9 + 9 = 4n + 2 + 9
5n = 4n + 11
take away 4n from from both sides of the equation
5n - 4n = 4n - 4n + 11
5n - 4n = 11
1n = 11
n = 11
Question 4 has the same values for question 3, they just changed n to a m
5m - 9 = 4m + 2
m = 11
Question 5
-2x + 3 = -3x - 1
Add 3x to both sides of the equation
-2x + 3x + 3 = -3x + 3x - 1
1x + 3 = -1
x + 3 = -1
Take away 3 from both sides of the equation
x + 3 - 3 = -1 - 3
x = -4
Question 6
7n + 8 = 6n + 4
Take away 6n from both sides of the equation
7n - 6n + 8 = 6n - 6n + 4
1n + 8 = 4
n + 8 = 4
Take away 8 from both sides of the equation
n + 8 - 8 = 4 - 8
n = -4
Question 7
m + 3 = -m - 1
Add 1m to both sides of the equation
m + 1m + 3 = -m + 1m - 1
2m + 3 = -1
Take away 3 from both sides of the equation
2m + 3 - 3 = -1 - 3
2m = -4
M + 4 = -M + 10
First reorganize the terms on the left side
M + 4 = 10 - M
Take away 4 from both sides
M + 4 - 4 = 10 - M - 4
M = 10 - M - 4
Combine positive 10 and negative 4
M = 6 - M
Add M to both of the sides
M + M = 6 - M + M
M + M = 6
2M = 6
Divide both sides by 2
2M/2 = 6/2
M = 3
Question 2
2x - 2 = x - 4
Take away 1x from both sides of the equation
2x - 2 = x - 4
2x - 1x - 2 = x - 1x - 4
1x - 2 = -4
x - 2 = -4
Add 2 to both of the sides of the equation
x - 2 + 2 = -4 + 2
x = -2
Question 3
5n - 9 = 4n + 2
Add 9 to both sides of the equation
5n - 9 + 9 = 4n + 2 + 9
5n = 4n + 11
take away 4n from from both sides of the equation
5n - 4n = 4n - 4n + 11
5n - 4n = 11
1n = 11
n = 11
Question 4 has the same values for question 3, they just changed n to a m
5m - 9 = 4m + 2
m = 11
Question 5
-2x + 3 = -3x - 1
Add 3x to both sides of the equation
-2x + 3x + 3 = -3x + 3x - 1
1x + 3 = -1
x + 3 = -1
Take away 3 from both sides of the equation
x + 3 - 3 = -1 - 3
x = -4
Question 6
7n + 8 = 6n + 4
Take away 6n from both sides of the equation
7n - 6n + 8 = 6n - 6n + 4
1n + 8 = 4
n + 8 = 4
Take away 8 from both sides of the equation
n + 8 - 8 = 4 - 8
n = -4
Question 7
m + 3 = -m - 1
Add 1m to both sides of the equation
m + 1m + 3 = -m + 1m - 1
2m + 3 = -1
Take away 3 from both sides of the equation
2m + 3 - 3 = -1 - 3
2m = -4